KUALITAS LINGKUNGAN PERAIRAN PANTAI DI SEKITAR LOKASI TAMBAK PERIKANAN KECAMATAN GEROKGAK KABUPATEN BULELENG BALI - Mustofa, Beny; Arthana, I Wayan; Watiniasih, Ni Luh (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2020)
The purpose of this study was to determine the quality of waters, community structure of phytoplankton and zooplankton around the fishponds waters of Gerokgak Subdistrict. This research was conducted for 2 months, from May to June 2019. There were three sampling locations, namely in Gerokgak, Patas and Sumberkima Villages. The research method used was field research using quantitative analysis of phytoplankton biological indice. The waters condition around the Gerokgak Subdistrict waters was rather polluted, except for the around Sumberkima Village waters. The quality of the waters of Sumberkima Village was better than that of Gerokgak Village and Patas Village waters. Plankton abundance in the waters of Sumberkima Village was slightly low. The highest abundance of plankton in the waters of Patas Village and the lowest in Gerokgak Village waters. The dominant type of plankton was Cyanophyceae (blue-green algae). Keywords: water quality; plankton; species; abundance.